The message of the prophets - von Rad, Gerhard, 1901-1971; Haller, Eduard; Stalker, D.M.G. (London, UK SCM, 1968)
Includes bibliographical references and indexes.
Originally published in German : Die Botschaft der Propheten.-- Munich : Siebenstern Taschenbuch Verlag, 1967, which is a revised version of material from Theologie des Alten Testaments. The complete English edition Old Testament Theology (vols. 1 and 2) is published by Oliver and Boyd, Ltd, London a newer edition of which is also held : Louisville, KN : Westminster 2002
Keywords: Bible. O.T. Prophetic books -- criticism, interpretation, etc